Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1136/gut.2007.125963
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drug-induced small intestinal damage is Toll-like receptor 4 dependent

Abstract: Indomethacin may injure the small intestine through a TLR4/MyD88-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
215
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 29 publications
9
215
0
5
Order By: Relevance
“…Several lines of evidence support this hypothesis: (i) neutrophil depletion by intraperitoneal injection of anti-neutrophil antibody significantly attenuates the intestinal mucosal injury induced by indomethacin (13,16); (ii) intravital microscopic evaluation of the mesenteric circulation has shown that indomethacin promotes neutrophil adherence and emigration in post-capillary venules (23); and (iii) the induction of intestinal TNF-α production by NSAIDs was followed by activation of the neutrophil activation pathway (MPO activity) in the inflammation cascade, which could contribute to jejunum-ileum lesions (11). In this study, we have shown that MPO activity, an index of tissue-associated neutrophil accumulation, and the expression of KC mRNA, which is involved in chemotaxis and cell activation of neutrophils, were remarkably enhanced in the indomethacin-treated intestinal mucosa, and that these increases were significantly reduced in TNF-α -/-mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Several lines of evidence support this hypothesis: (i) neutrophil depletion by intraperitoneal injection of anti-neutrophil antibody significantly attenuates the intestinal mucosal injury induced by indomethacin (13,16); (ii) intravital microscopic evaluation of the mesenteric circulation has shown that indomethacin promotes neutrophil adherence and emigration in post-capillary venules (23); and (iii) the induction of intestinal TNF-α production by NSAIDs was followed by activation of the neutrophil activation pathway (MPO activity) in the inflammation cascade, which could contribute to jejunum-ileum lesions (11). In this study, we have shown that MPO activity, an index of tissue-associated neutrophil accumulation, and the expression of KC mRNA, which is involved in chemotaxis and cell activation of neutrophils, were remarkably enhanced in the indomethacin-treated intestinal mucosa, and that these increases were significantly reduced in TNF-α -/-mice compared with WT mice.…”
Section: Discussionmentioning
confidence: 60%
“…Several reports have demonstrated the increases in intestinal TNF-α mRNA expression in this model of small intestinal injury (13). Watanabe et al (13) demonstrated that the expression of TNF-α was increased in the small intestine after indomethacin treatment through a Toll-like receptor (TLR) 4-dependent pathway. Bertrand et al (11) also reported that TNF-α production was linked to the toxicity of indomethacin in the small intestine, especially at the early stage of the ulcerogenic process, and that the inhibition of TNF-α synthesis reduced indomethacin-induced intestinal injury in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well that NSAIDs do not induce small-bowel injury in germ-free animals [20]. Watanabe et al reported that lipopolysaccharides (LPS)/toll-like receptor 4 (TLR4)/ MyD88-dependent signaling pathway plays an important role in the development of such injuries [32]. Acid is closely involved in gastric mucosal injury.…”
Section: Present Status Of Small Intestinal Mucosal Injury Caused By mentioning
confidence: 99%